Introduction to electronics - Gates, Earl D. , 1945- (Delmar Cengage Learning, 2012)
Introduction to electronics provides readers with a broad overview of both the linear and digital fields of electronics while also providing the basics so they can understand the fundamentals of electronics. This book is intended for first year students or users to stimulate their interest in electronics, whether they are in high school, college or the field, and will provide them with a fundamental background in electronics that they need to succeed in today's increasingly digital world. The sixth edition continues to expose readers to the broad field of electronics at a level that they can easily understand. Chapters are brief and focused and frequent examples are used to show math and formulas in use. Each chapter builds on the previous chapter to allow readers to grow with the knowledge necessary to continue. There are many new problems and review questions and Internet applications that enhance readers' learning and retention of the material. In addition, new photographs keep them up to date with changes in the field of electronics and a new topic on Programmable Interface Controllers (PICs) is included as well